POLITIK BLATER DALAM PERSPEKTIF uu. PEMILU NO.7 TAHUN 2017: - Najmi, Alfin; Ibad, Syahrul; Dairani, Dairani (HUKMY : Jurnal Hukum, 2024)
In the life of Madurese society, there is a figure who has quite a strong influence in the world of politics, which is commonly known by the Madurese community as a blater figure. The involvement of blater in politics, especially in Madura, has become a natural and common thing because based on the influence they have, the involvement of blater can facilitate efforts to obtain and collect as many community votes as possible in an election such as in the DPRD or Regent elections, because blater figures are usually respected and feared by the community so that most of them already have a mass that is one of the main capitals in politics. But unfortunately the political practices implemented by blater during elections are identical to acts of violence and intimidation.